A pan-cancer analysis revealed the role of the SLC16 family in cancer. Issue 1 (1st January 2021) - Li, Jun; Xie, Jiaheng; Wu, Dan; Chen, Liang; Gong, Zetian; Wu, Rui; Hu, Yiming; Zhao, Jiangning; Xu, Yetao
ABSTRACT: Cancer is one of the serious diseases that endanger human health and bring a heavy burden to world economic development. Although the current targeted therapy and immunotherapy have achieved initial results, the emergence of drug resistance shows that the existing research is far from enough. In recent years, the tumor microenvironment has been found to be an important condition for tumor development and has profound research value. The SLC16 family is a group of monocarboxylic acid transporters involved in cancer metabolism and the formation of the tumor microenvironment. However, there have been no generalized cancer studies in the SLC16 family. In this study, we conducted a pan-cancer analysis of the SLC16 family. The results showed that multiple members of the SLC16 family could be used as prognostic indicators for many tumors, and were associated with immune invasion and tumor stem cells. Therefore, the SLC16 family has extensive exploration value in the future.